The Impact of China Shock on Deindustrialisation over time - Nugraheni Dwi Utami, Nugraheni Dwi Utami (AFEBI Economic and Finance Review, 2019)
Abstract This paper analyses the impact of Chinese import competition on deindustrialization measured by real value added and employment share in 61 developed and developing countries over 1970-2010 period. By employing quantile regression with instrumental variables to correct potential endogeneity bias, the results suggest that the main driver of deindustrialization in employment in developed countries is technological change. There is heterogeneous effect of China shock. In developed countries, the effect is destructive in term of both employment and real value added in the lower quantile of distribution, with the higher magnitude for the former. In the higher quantile, complementary effect outweighs detrimental impact. In developing countries, the negative effect of China’s shock on real value-added rises as the increase in the proportion of manufacturing value-added in countries. The destructive effect on employment in developing countries seems to be harder after 1990 period. Keywords : China; competition; deindustrialization